Understanding Celiac Disease by Genomics. Issue 5 (May 2016) - Withoff, Sebo; Li, Yang; Jonkers, Iris; Wijmenga, Cisca
Abstract : Celiac disease (CeD) is a complex immune-mediated disease. Genetic studies have implicated 43 predisposing loci that collectively explain some 50% of the genetic variance in CeD. More than ∼90% of CeD-associated single nucleotide polymorphisms (SNPs) localize to the non-coding genome, which we need to better understand to translate genetic knowledge into clinical practice. New genomic technologies and resources are permitting a systematic analysis of the functional elements in the non-coding part of the genome. Here we explain how investigating the regulatory and epigenomic landscape will help to pinpoint the cell types involved in CeD, and the driver genes and gene regulatory networks that are affected by CeD-associated SNPs. Trends: The majority of CeD SNPs intersect with promoter and enhancer sequences, thereby deregulating the expression of genes encoding proteins or regulatory RNAs such as miRNAs and lncRNAs. Integration of publicly available data with genotyping results and eQTL mapping strategies has led to the implication of more cell types in CeD and to the prioritization of disease-predisposing SNPs and genes. Mapping of eQTL genes using publicly available RNA-seq data has led to a significant increase in the number of known CeD-associated eQTL effects. Single-cell sequencing of patient-derived biopsies or blood is likely to reveal immune cell subpopulations that are uniquely associated with CeD. To study the effects of individual disease-associated SNPs, CRISPR/Cas9 technology now allows disease-associated risk SNPs to be introduced into or removed from primary immune cells.